2017
DOI: 10.1001/jama.2017.15927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Increases in US Health Care Spending, 1996-2013

Abstract: Increases in US health care spending from 1996 through 2013 were largely related to increases in health care service price and intensity but were also positively associated with population growth and aging and negatively associated with disease prevalence or incidence. Understanding these factors and their variability across health conditions and types of care may inform policy efforts to contain health care spending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
230
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(242 citation statements)
references
References 25 publications
9
230
1
2
Order By: Relevance
“…During a similar period, from 2001/2002 to 2009/2010, we find health status and all treated conditions (not just chronic) explained 45.0 percent of expenditure growth, with all other individual characteristics contributing less than one percent. In contrast, Dieleman et al found that age, sex and underlying or true prevalence of conditions together explained less than 10 percent of per capita prescription drug growth between 1996 and 2013.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…During a similar period, from 2001/2002 to 2009/2010, we find health status and all treated conditions (not just chronic) explained 45.0 percent of expenditure growth, with all other individual characteristics contributing less than one percent. In contrast, Dieleman et al found that age, sex and underlying or true prevalence of conditions together explained less than 10 percent of per capita prescription drug growth between 1996 and 2013.…”
Section: Discussionmentioning
confidence: 92%
“…Roehrig and Daly show that treated prevalence increased more rapidly than underlying or true prevalence for diabetes, hypertension, and hyperlipidemia between 1999/2000 and 2011/2012. More research is needed to assess whether trends such as these explain why Dieleman et al found smaller impacts of underlying conditions compared to studies examining treated conditions—and whether convergence of treated and underlying conditions may now be helping to limit further condition‐driven increases in use to the growth in underlying condition prevalence. A better understanding of these forces may help us to better predict future prescription drug spending growth and to devise policies that would help control that growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lower healthcare expenditures per capita was a predictor of musculoskeletal imaging authority, it cannot indicate causation within the limits of our study. A multitude of factors influence a nation's healthcare expenditures (Dieleman et al, ; J. L. Dieleman et al, ; Johansen, ). Further research is needed to determine if healthcare expenditures per capita are a contributing factor to determining physical therapy legislation or if existing legislation contributes to lower expenditures via an elimination in redundant appointments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent international comparison found that, while Americans visit doctors and hospitals at similar rates to citizens of other high income countries, they pay a higher unit price for each intervention 2. This simple truth—often overlooked in health policy discussions—drives higher overall healthcare spending in the United States 34…”
mentioning
confidence: 99%